The Role of Artificial Intelligence in Enhancing Cyber Security using Deep Learning Techniques: A Review - Abeer Alyoons; sabren altai (Al-Rafidain Journal of Computer Sciences and Mathematics)
Learning AI is used to detect various cyber-attacks, malicious attacks and unusual future threats in the network. Notice the pattern in which any illegal or suspicious activities behave, recognize what is needed, and identify proactive behaviours that indicate the presence of threats. In light of this, the two researchers provide an in depth review of research related to artificial intelligence in cyberspace and through learning techniques used to train machines to enhance cyber security. The studies that were used, the techniques, the extent of their effectiveness and efficiency in achieving the desired goal were reviewed, detailed, sorted and compared with each other, especially the data used to build the model and the diversity of these methods that were used to create its model.